Pathways Linking Childhood Maltreatment to Impulsivity: The Mediating Role of Affect Balance. Issue 8 (14th September 2021) - Heshmati, Rasoul; Haghi, Negin; Brownridge, Douglas A.
ABSTRACT: The present study tested whether the relationship between childhood maltreatment and impulsivity could be explained by affect balance in college students. In a cross-sectional study, 250 college students were recruited from the University of Tabriz, Iran. Participants completed self-report scales, including the Persian version of the Child Abuse Self-Reported Scale, Barratt's Impulsivity Scale, as well as the Positive & Negative Affect Scale. A Structural Equation Model (SEM) was used to empirically explore relationships. The model of affect balance as a mediator between childhood maltreatment and impulsivity fit the data. Respondents that had a higher level of childhood maltreatment reported a higher level of impulsivity. Childhood maltreatment showed a significant negative effect on affect balance. Also, affect balance was negatively associated with greater levels of impulsivity. Bootstrapping results showed an indirect effect of childhood maltreatment on impulsivity via affect balance. Findings suggest that affect balance may explain the relationship between childhood maltreatment and impulsivity in college students. Training in affect balance may decrease impulsivity in individuals who experienced childhood maltreatment.